2016
DOI: 10.1002/elps.201600369
|View full text |Cite
|
Sign up to set email alerts
|

Highly multiplex and sensitive SNP genotyping method using a three‐color fluorescence‐labeled ligase detection reaction coupled with conformation‐sensitive CE

Abstract: For the development of clinically useful genotyping methods for SNPs, accuracy, simplicity, sensitivity, and cost-effectiveness are the most important criteria. Among the methods currently being developed for SNP genotyping technology, the ligation-dependent method is considered the simplest for clinical diagnosis. However, sensitivity is not guaranteed by the ligation reaction alone, and analysis of multiple targets is limited by the detection method. Although CE is an attractive alternative to error-prone hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It has been reported that SNPs are frequently difficult to distinguish because of differences in only one base in the DNA sequence, corresponding to different alleles [ 16 ]. The specificity, sensitivity, and cost-effectiveness of method designs are decisive measures for improving SNP detection [ 17 , 18 ]. Moreover, it is crucial to exploit efficient assessment methods to detect SNPs in complicated genomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SNPs are frequently difficult to distinguish because of differences in only one base in the DNA sequence, corresponding to different alleles [ 16 ]. The specificity, sensitivity, and cost-effectiveness of method designs are decisive measures for improving SNP detection [ 17 , 18 ]. Moreover, it is crucial to exploit efficient assessment methods to detect SNPs in complicated genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry based methods 47 , 48 are limited by expensive instruments and the difficulty of the use of large-scale equipment for clinical testing. Capillary electrophoresis (CE) 49 – 51 has been used for the multiplex detection of nucleic acids. The capability of CE for multiplex detection is related to its highly effective separation ability, so it can easily achieve real high-throughput detection.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex ligation-dependent probe amplification (MLPA) is a reliable and efficient technique for the detection of multiple gene mutations. , Specific probes with unique lengths were designed for different targets so that the PCR products of the ligated probes could be separated by CE. Another CE-based technique for multiple SNPs detection is primary PCR coupled with ligase detection reaction (LDR). , These CE-based assays have LODs of about 1–5% for multiple mutant alleles and are inadequate for early diagnosis testing.…”
mentioning
confidence: 99%